Oxygen Uptake Rate As An In-Situ Indicator For Shock Loading Event At Sewage Treatment Plant - Khazali, Aliff Izuddin (Universiti Sains Malaysia, 2021)
Sewage is related to human waste, solid waste, chemicals, oil, and this discharge will return to the hydrological cycle. Therefore, it is essential for the engineer to participate in sewage management and requisite knowledge of the sewage system. To treat the sewage, many processes need to be done to ensure that the efficient sewage treatment plant is always at its peak; a suitable control parameter is important for this case. There are many control parameters such as Oxygen Uptake Rate, Sludge Volume Index, Food to Microorganisms, and Specific Oxygen Uptake Rate. This study will discuss the oxygen uptake rate as an in-situ for shock loading event at a sewage treatment plant. In a sewage treatment plant, identifying the problem and crucial monitoring parameters is crucial to understanding the treatment process needed for the treatment plant. Nowadays, many types of the process can be used to treat sewage, such as Conventional Activated Sludge and Aerobic Granular Sludge process. Hence, engineers need the ability to differentiate the crucial operating and monitoring parameters for the process. This study also focuses on the relationship between the shock loading and Oxygen Uptake Rate as monitoring parameters using secondary data. These monitoring parameters will help the engineer to understand the influent that come to the Sewage Treatment Plants from the household or industry. Using the SPSS and excel, the data taken from Awang (2016) will be analysed to see the relationship between recommended parameters and Organic Loading Rate. The fluctuation of the sewage can cause many problems to the STP as it may cause an overflow of sewage, especially during a rainy day. The analysis method is by using Descriptive analysis, Pearson's Correlation, Spearman's Correlation, Covariance, T-Test Paired Two Sample for Means, and Regression. This test has been conducted to test the which the null hypothesis can be rejected or not. The result from the T-test paired two samples for means shows that the Oxygen Uptake Rate, Sludge Volume Index, Mixed Liquor Suspended Solid, and Food to Microorganism ratio is superior to the Organic Loading Rate as a monitoring parameter to the fluctuated Organic Loading Rate with 0.01925, 0.02198x10-2, 0.01147, and 0.02826, respectively. All of this value is below 0.05, which the null hypothesis of the t-test can be rejected. As a summary, this study shows that Oxygen Uptake Rate, Sludge Volume Index, Mixed Liquor Suspended Solids, and Food to Microorganism ratio can be a parameter to monitor the actual influent condition of the Aerobic Granular Sludge system as the data from Awang (2016) were using the Sequencing Batch Reactor to gain the result.